Upaya Meningkatkan Kompetensi Guru Melalui Penerapan Metode CLCK (Contoh, Latihan, Control, Kerja Mandiri) di SDN Rebalas III Grati Kabupaten Pasuruhan - Musdalifah, Ghonik (LPPM Universitas Bina Bangsa, 2022)
The preparation of learning implementation plans is very important, because good learning management greatly influences the preparation of learning implementation plans according to indicators. The advantage of CLCK is that teachers are given examples in making lesson plans and after that they practice with the principal and the activities carried out do not depend on others. To overcome this, it is necessary to strive for CLCK coaching (Examples, Training, Control, Independent Work) in the RPP preparation program to improve teacher competence. Teachers who are classified as very active are 2 people or 25% and classified as less active are 4 people or 75%, based on the results of observations in cycle I. The advantages of cycle I - 2 teachers are very active based on the analysis of observations. Weaknesses of cycle I, while 4 people were less active based on observations, especially on aspects of teacher interaction with school principals, group collaboration, activities in group discussions so that it was continued in cycle II, regarding the CLCK Guidance Model in the RPP Preparation Program at SDN Rebawa 3 District Free Pasuruan Regency. Coaching activities at the sub-district level for cycle II were carried out in October 2019 3 times. Teachers who are classified as very active are 1 person and classified as active 5 people, based on the results of observations in cycle II. Class teachers at SDN Rebalsa 3, Grati District, Pasuruan Regency have been creative in making Learning Implementation Plans, so the CLCK Guidance Model in the Program for Developing Learning Implementation Plans at SDN Relaba 3 Sub-district Grati Pasuruan Regency can improve teacher competence and teacher opinions are very useful for CLCK development in the program for organizing elementary school teaching and learning guided by the author